ECOLOGICAL CONSEQUENCES OF DEVELOPMENT OF ORES POTASSIUMS ON DOMBROVSKY QUARRY - Семчук, Я. М.; Боднар, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The brief characteristics of the influence Dombrovsky of quarry on the ecological state|figure,camp,mill| of environment of Kalush| region. The catastrophic situation of potassium quarry is appraised with a purpose of warning extraordinary situations and working out rational measures preventing their appearance in time has been done. Warnings are done in relation to|concerning| the breach of brines in aquiferous horizon, in fact concentration| of waters is multiplied with every day.